DERAJAT INFEKSI DAN TINGKAT PREVALENSI CACING Anisakis sp PADA IKAN TONGKOL (Euthynnus affinis) DI TPI KOTA PEKALONGAN - Linayati - Linayati (Fakultas Perikanan Universitas Pekalongan, 2018)
The objective of this study was to look at the degree of infection and the prevalence of anisakis presence in the body of Euthynnus affinis . research was conduct in March - April 2017 at TPI (fish auction) of Pekalongan city. The length of fish used are 19-24 cm fish as the first group and 25-33 cm as the second group. The number of fish used as many as 50 fish that is divided into 2 groups as above. In this study, observation of the presence of anisakis worms carried on the organs in the fish body of the intestine, stomach, liver and fish muscles. The results showed that the degree of fish infection was 12.6 in size 19-24 cm, while the degree of infection in the 25-33 cm group was 16.5. While the prevalence value in fish group size of first 60% and group size second 88%. The value belongs to the highly infection criteria. The largest amount of anisakis found in the gut organs because on that organs is full of food which needed to grow for parasit. In both groups of anisakis worms found in the intestine more than 100, while in the liver ranged from 10 to 36.